2012
DOI: 10.1167/iovs.11-8363
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Patterns (POP): A Machine Classifier Algorithm to Identify Glaucoma Progression in Visual Fields

Abstract: POP, with its display of DOC of progression and its identification of progressing VF defect pattern, adds to the information available to the clinician for detecting VF progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…We also compared the GEM-POP outcome to the recently developed VIM progression of patterns (VIM-POP) method [19], for the same eyes and for the same follow-up duration, and found that GEM-POP performed slightly but not significantly better than VIM-POP (sensitivity for VIM-POP was 26.6% compared to 28.9% for GEM-POP).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We also compared the GEM-POP outcome to the recently developed VIM progression of patterns (VIM-POP) method [19], for the same eyes and for the same follow-up duration, and found that GEM-POP performed slightly but not significantly better than VIM-POP (sensitivity for VIM-POP was 26.6% compared to 28.9% for GEM-POP).…”
Section: Resultsmentioning
confidence: 99%
“…The VFI and MD are global indices provided for each individual test. We also compared the performance of GEM with that of the previously described VIM-based method [19]. We will provide the details of the assessments in the subsequent sections.…”
Section: Glaucoma Progression Detection Pipelinementioning
confidence: 99%
See 3 more Smart Citations